Sosialisasi Pemanfaatan AI untuk Meningkatkan Partisipasi Siswa dalam Pembelajaran di SMPN 5 Tualang - Agustiani, Aulia; Putri, Hikmah Zalifah; Putra, Yusa; Rery, Nurul Masyithah; Ramdha, Triana (Universitas Pahlawan Tuanku Tambusai, 2025)
Artificial intelligence (AI) has great potential in enhancing the effectiveness of learning, particularly in addressing the needs of the Alpha generation, who are deeply connected to digital technology. This community service activity aims to familiarize teachers of SMPN 5 Tualang with the use of AI technology, to increase student participation in the learning process. The methods used include initial surveys, socialization through lectures and discussions, and hands-on practice with relevant AI applications. The results of the activity showed that most participants experienced an increase in understanding of the concept and implementation of AI, and showed high enthusiasm for applying it in learning. The implementation of this activity has made a real contribution to encouraging digital transformation in the junior high school environment.